The medical interview the three function approach - Cole, Steven A. (Elsevier, Saunders, 2014)
Equips you to communicate effectively with your patients so you can provide optimal care. This book presents a practical, systematic approach to honing your basic interviewing skills and managing common challenging communicating situations.